Efficacy of a single antimicrobial photodynamic therapy session as an adjunct to non-surgical periodontal therapy on clinical outcomes for periodontitis patients. A systematic review - Atarchi , Ahmed R; Atarchi , Zaid R (Journal of Baghdad College of Dentistry, 2023)
Background: periodontitis is a multifactorial and multi-etiological disease associated with destructive events to the periodontium. Non-surgical periodontal therapy (NSPT) is considered an efficient, gold-standard approach to treat this disease; however, several variables could hinder the success rate. Combining antimicrobial photodynamic therapy (aPDT) with NSPT showed promising results but the available literature show variations in results. Aim: whether using single episode of aPDT as adjunct to NSPT for adults affected by periodontitis can improve clinical outcomes, with a minimum 3 months follow up after terminating active treatment, as compared to conventional manual instrumentation? Methods: Three databases (PubMed, ScienceDirect, and Cochrane Library) were searched to retrieve relevant articles. The keywords matrix used for the search process consisted of the following terms: periodontitis OR periodontal disease AND photodynamic therapy OR antimicrobial photodynamic therapy OR Laser. Results: A total of 4104 articles were retrieved from the search process for the last 10 years. After removing duplicates and applying filters, 44 article were eligible for full-text reading. The last step resulted in 6 randomized controlled trials that were used for data synthesis. Conclusions: Retrieved data from this study indicated that adjunctive aPDT has a potential beneficial effect on short-term mainly reflected by improving bleeding scores and microbiological outcomes for patients with periodontitis. However, longer term advantage was not evident as compared to conventional periodontal therapy. Further studies are advised to draw a solid conclusion about using aPDT as adjunct to NSPT